2021
DOI: 10.3390/jof8010007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Factors and Copper on the Regulation of Laccase Enzyme Production in Pleurotus ostreatus

Abstract: This research aimed to establish the relationship between carbon–nitrogen nutritional factors and copper sulfate on laccase activity (LA) by Pleurotus ostreatus. Culture media composition was tested to choose the nitrogen source. Yeast extract (YE) was selected as a better nitrogen source than ammonium sulfate. Then, the effect of glucose and YE concentrations on biomass production and LA as response variables was evaluated using central composite experimental designs with and without copper. The results showe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…P. ostreatus cultivation has led to a maximum biomass production of 18 g L −1 at a combination of 45 g L −1 glucose and 15 g L −1 yeast extract. 46 In another study using a lower range of yeast extract concentrations (1.0 to 5.0 g L −1 ) in the culture medium for P. ostreatus growth, a low value (1.72 g L −1 ) of biomass production was achieved at 40 g L −1 glucose and 3.0 g L −1 yeast extract. 47 Concerning the submerged cultivation of Tuber sinense , the maximum biomass production (24.8 g L −1 ) was found when glucose and yeast extract concentrations were 60 g L −1 and 30 g L −1 , respectively.…”
Section: Resultsmentioning
confidence: 98%
“…P. ostreatus cultivation has led to a maximum biomass production of 18 g L −1 at a combination of 45 g L −1 glucose and 15 g L −1 yeast extract. 46 In another study using a lower range of yeast extract concentrations (1.0 to 5.0 g L −1 ) in the culture medium for P. ostreatus growth, a low value (1.72 g L −1 ) of biomass production was achieved at 40 g L −1 glucose and 3.0 g L −1 yeast extract. 47 Concerning the submerged cultivation of Tuber sinense , the maximum biomass production (24.8 g L −1 ) was found when glucose and yeast extract concentrations were 60 g L −1 and 30 g L −1 , respectively.…”
Section: Resultsmentioning
confidence: 98%
“…( 2017 ) demonstrated that fungal extracellular laccase production is sensitive to the presence of other fungi, providing a potential link between the upregulation of laccase and melanogenesis, but their complete regulatory mechanisms are yet unclear. Much work has been done exploring the characterization of and possible means of regulating extracellular laccases in fungi (Durán-Sequeda et al., 2022 ; Eggert et al., 1996 ; Flores et al., 2009 ; Janusz et al., 2020 ; Lonergan & Baker, 1995 ; Minussi et al., 2007 ; Palmieri et al., 2000 ; Peña et al., 2021 ), but few studies have explored the capabilities of these laccases to participate in melanogenesis. Independent work by both Jia et al.…”
Section: Extracellular Fungal Eumelanin Productionmentioning
confidence: 99%
“…An increase of 10-fold and 1.4-fold in laccase activity has been registered at 1 mM CuSO 4 in Pleurotus ostreatus [ 42 ] and white rot fungus WR-1 [ 43 ], respectively. Variations in terms of the effect of copper addition on laccase activity and isoenzymatic patterns from Pleurotus sajor-caju , as laccase activity increased 2.3 and 1.3-fold in cultures supplemented with 0.5 and 1 mM CuSO 4 , respectively, and correlation with two isoenzymes of 65 kDa and 35 kDa shown by zymogram analysis has been reported [ 44 ].…”
Section: Discussionmentioning
confidence: 99%